Post-Olympic use of the Olympic venues: The case of Greece - Kasimati, E. (Athens Journal of Sport, 2015)
The 2004 Athens Olympic Games provided the host city with a unique challenge to ensure long-term benefits and to present itself worldwide as a modern, well designed and well run metropolis with infrastructure and state-of-the-art facilities, promoting the quality of life for its residents, as well as its economic and cultural development. The way however that the huge and costly sports facilities, unanimously acknowledged as a burden on the national economy and the Greek taxpayers, were to be used and exploited after the Games, became a headache to all post-games governments. The post-Olympic era was largely characterised by the incapability of the government to productively utilize the extensive infrastructure of the Olympic games. The bureaucracy and the lack of governmental long-term planning, left most venues unexploited and abandoned right after the games. Hellenic Olympic Properties (HOP), a government-controlled company responsible for making use of each of the Olympic venues after the games was extremely slow and inefficient in the utilization of its assets, while its annual published financial statements revealed consistently negative bottom lines. Seven years after the games, the reality is that the expected benefits from the post-Olympic use of the facilities to the Greek economy still remain to be seen.